Rules of engagement and the international law of military operations - Hosang, J. F. R. Boddens (Oxford : Oxford University Press, 2020)
This volume systematically analyses rules of engagement (ROE), a crucial component of the legal framework in which every soldier operates. It explains how such rules operate in both the legal context and military operational world, and how ROE are applied in practice.
This edition also issued in print: 2020.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on February 10, 2020).
Keywords: War (International law); Humanitarian law